A 3-O-methylated heterogalactan from Pleurotus eryngii activates macrophages. (15th February 2019) - Yan, Jingmin; Meng, Yue; Zhang, Mengshan; Zhou, Xiaohuan; Cheng, Hairong; Sun, Lin; Zhou, Yifa
Highlights: A novel heterogalactan (WPEP-N-b) was purified from Pleurotus eryngii. 3-O-methyl-galactose was determined by LC-MS in WPEP-N-b. WPEP-N-b increased macrophage phagocytosis, secretion of NO and cytokines. Macrophage activation was through MAPKs, NF-κB pathways via TLR2 receptor. Abstract: Mushroom-derived polysaccharides exhibit various biological activities owing to their diverse structural features. Here, we purified a 3-O-methylated heterogalactan (WPEP-N-b, Mw 21.4 kDa) from the fruiting bodies of Pleurotus eryngii . WPEP-N-b is composed primarily of galactose (43.8%), mannose (39.3%), methyl-galactose (11.7%) and glucose (9.2%) residues, with the main chain being composed of α-1, 6-linked D-Gal p and 3-O-Me-D-Gal p, branched at O-2 with single t-β-D-Man p as major the side chain. β-1, 6-D-Glc p residues are present as minor components either in side-chains or backbone. WPEP-N-b increases macrophage phagocytosis and secretion of NO, TNF-α, IL-6 and IL-1β. Mechanistic studies demonstrate that WPEP-N-b promotes the degradation of IκB-α, and enhances phosphorylation of MAPKs and the NF-κB p65 subunit. Our results also indicate that this polysaccharide activates RAW264.7 cells via MAPK and NF-κB signaling pathways and the Toll-like receptor 2(TLR2). These results increase our understanding as to how mushroom-derived polysaccharides modulate the immunologic process.